The implications of TARGET2 in the European balance of payments crisis and beyond - Sergio Cesaratto (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
The paper provides an account of the meaning and implications of TARGET2 in the eurozone (EZ) balance of payments crisis. In this context, it discusses Hans-Werner Sinn's thesis about a stealth bail-out of the EZ periphery by the ECB from a heterodox perspective. Financial liberalisation, a relatively loose monetary policy and the provisional fading of devaluation risks generated ephemeral growth in some peripheral EZ countries sustained by capital flows from core countries. This has been followed by real exchange rate revaluation and deterioration of foreign accounts. As a result, external financing flows dried up and the previous stock of loans began to be repatriated. TARGET2 has played a fundamental role in avoiding a precipitous crisis. This distinguishes the European crisis from more traditional balance of payments crises. However, the presence of TARGET2 does not offset the absence of the financial crisis prevention and resolution mechanisms that are characteristic of fully fledged political and currency unions.
Keywords: E11; E12; E42; E58; F32; F33; F34; F36; N24; 330; European Monetary Union; financial crisis; Germany; neo-mercantilism; balance of payment; capital flows; sudden stops; TARGET2; OMT